How is ecosystem health defined and measured? A critical review of freshwater and estuarine studies. (October 2016) - O'Brien, Allyson; Townsend, Kallie; Hale, Robin; Sharley, David; Pettigrove, Vincent
Abstract: Assessing ecosystem health is an ongoing priority for governments, scientists and managers worldwide. There are several decades of scientific literature discussing ecosystem health and approaches to assess it, with applications to aquatic and terrestrial environments incorporating economic, environmental and social processes. We conducted a systematic review of studies that assess ecosystem health to update our current understanding of how ecosystem health is being defined, and provide new ideas and directions on how it can be measured. We focused the review on studies that used the term 'ecosystem health' or the equivalent terms 'ecosystem integrity', 'ecosystem quality' and 'ecosystem protection', in lotic freshwater and estuarine environments, and examined how many of these included explicit definitions of what ecosystem health means for their study system. We collected information about the temporal and geographical distribution of studies, and the types of indicators (biological, physical or chemical) used in the assessments. We found few studies clearly defined ecosystem health and justified the choice of indicators. Given the broad use of the term it seems impractical to have an overarching definition of ecosystem health, but rather an approach that is able to define and measure health on a case by case basis. A combination of biological, physical and chemical indicators was commonly used to assess ecosystem health in both estuarine and freshwater studies, with a strong bias towards fish and macroinvertebrate community metrics (e.g. diversity, abundance and composition). We found only two studies that simultaneously considered both freshwater and estuarine sections of the ecosystem, highlighting the significant knowledge gap in our understanding of the transfer of flow, nutrients and biota between the different systems—all key factors that influence ecosystem health. This review is the first to combine knowledge from both freshwater and estuarine ecosystem assessments and critically review how aquatic ecosystem health is defined and measured since the late-1990s, providing the basis for setting achievable management goals relating to ecosystem health into the future.